Effect of RuO2 in the shape selectivity of submicron-sized SnO2 structures - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Journal of Physical Chemistry B, 2005)
Several dissimilar types of tin oxide microstructures including bipyramids, cubes, and wires synthesized effectively by means of a simple approach were investigated using X-ray diffraction (XRD), thermogravimetry/ differential thermometric analysis (TG-DTA), and X-ray photoelectron spectroscopy (XPS). A possible growth mechanism is proposed using the results of these studies. The texture coefficient values of all the structures, indexed to a tetragonal lattice, exhibit amazing variation in the preferred orientation with respect to their shapes. Although XPS data indicate that wires and cubes have a strong SnO2 type signal, bipyramids interestingly exhibit both SnO and SnO2 signals and a correlation of the binding energy helps in understanding the growth kinetics of such submicron structures. The. results suggest that the bipyramids are formed because of the vapor-solid process (VS) while wires and cubes are formed by the vapor-liquid-solid (VLS) progression.

Room temperature nitric oxide sensor actualized from Ru-doped SnO2 nanowires - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Sensors and Actuators B - Chemical, 2005)
We report synthesis of the novel Ru-doped SnO2 nanowires and their distinctive response towards NO., and liquefied petroleum gas (LPG) in air. These nanowires have been prepared by a simple approach of evaporation of metal oxide at elevated temperature, The sensor exhibits three order of magnitude changes in the conductivity on exposure to NO2 in air at room temperature, Furthermore. Ru being one of the excellent sensitizers towards LPG these wires also exhibits sensitivity at 250&DEG; C. The amount of Ru plays a crucial role in modulating the sensitivity and lowering the operating temperature. © 2005 Elsevier B.V. All rights reserved.
Keywords: LPG; Nanowires; NO2; tin oxide ruthenium oxide

Liquid phase oxidation of alkanes using Cu/Co-perchlorophthalocyanine immobilized MCM-41 under mild reaction conditions - Karandikar, Prashant R.; Chandwadkar, Asha J.; Agashe, M.; Ramgir, N. S.; Sivasanker, S. (Applied Catalysis A-General, 2006)
{Amino-functionalized MCM-41 (NH2-MCM-41) was used to immobilize CU/CO-Cl16PC complex, i.e. Cu/Co-AM(PS) for liquid phase oxidation of alkanes under mild reaction conditions. Higher rates of reaction and better catalytic activity values were obtained for Cu/Co-AM(PS) as compared to Cu/Co-Cl16PC grafted on (i) amino-functionalized SiO2 [
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction